2000
DOI: 10.1098/rstb.2000.0579
|View full text |Cite
|
Sign up to set email alerts
|

T–cell memory: lessons from Epstein–Barr virus infection in man

Abstract: Epstein-Barr virus offers an ideal opportunity to follow the human T-cell response to a virus infection over time from its acute primary phase, as seen in infectious mononucleosis patients, into the memory phase that accompanies life-long virus persistence. Here we review recent evidence on the development and maturation of cytotoxic T-cell memory using this viral system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 62 publications
(88 reference statements)
1
17
1
Order By: Relevance
“…Our data raise the possibility that the lytic infection may play an important role in the establishment of latency by eliciting strong immunity and thus diverting the host immune response away from the latent infection. This possibility is supported by the observation that the early immune response to EBV is largely directed toward lytic viral epitopes, and T cells specific for latent epitopes are infrequent or absent during infectious mononucleosis (38,39). In the ␥HV68 system, T cells responding to the only known latent epitope are not detectable in the lung, mediastinal lymph node, or spleen until 19 days after infection (40).…”
Section: Discussionsupporting
confidence: 51%
“…Our data raise the possibility that the lytic infection may play an important role in the establishment of latency by eliciting strong immunity and thus diverting the host immune response away from the latent infection. This possibility is supported by the observation that the early immune response to EBV is largely directed toward lytic viral epitopes, and T cells specific for latent epitopes are infrequent or absent during infectious mononucleosis (38,39). In the ␥HV68 system, T cells responding to the only known latent epitope are not detectable in the lung, mediastinal lymph node, or spleen until 19 days after infection (40).…”
Section: Discussionsupporting
confidence: 51%
“…This loss of function in the presence of persistent Ag follows a progression in the sequence of cytotoxicity, IL-2, TNF-␣, and IFN-␥ production, exhaustion, and deletion (20,21). However, these findings appear to be at odds with situations where viruses persist and CD8 ϩ T cell functions are not apparently compromised (22)(23)(24)(25), with reports of residual Ag presentation (26) or with a possible role for Ag in the maintenance of immunological memory (27). ␥-herpesviruses (␥HV) are characterized by the establishment of lifelong asymptomatic infection, the persistence in Ͼ90% of the human population, and the association with a large list of life-threatening conditions (28,29).…”
Section: The Contribution Of Memory Cd8contrasting
confidence: 48%
“…In The Netherlands, a cross-sectional serum study in 1991 had shown that 40% is EBVseropositive at 10 years of age increasing to 98% at 30 years, while CMV immunity is detected in ϳ30 and 50%, respectively (14). Infection with these viruses early in life is most often asymptomatic, while infection later in life is a self-limiting disease more often associated with clinical symptoms (12). On the other hand, chickenpox (varicella) is a common disease of childhood caused by primary infection with VZV, a highly contagious herpesvirus with attack rates of Ͼ85% in susceptible contacts in the temperate climate under 7 years of age (15)(16)(17).…”
Section: Frequencies Of Circulating Cytolytic Cd45ramentioning
confidence: 99%
“…Both EBV and CMV are herpesviruses that infect the vast majority of humans, following a bimodal pattern of infection with peaks during early childhood and late adolescence, being defined to a large extent by socioeconomic factors (12,13). In The Netherlands, a cross-sectional serum study in 1991 had shown that 40% is EBVseropositive at 10 years of age increasing to 98% at 30 years, while CMV immunity is detected in ϳ30 and 50%, respectively (14).…”
Section: Frequencies Of Circulating Cytolytic Cd45ramentioning
confidence: 99%